Characteristics of Economic Security of Regions According with Their Social and Economic Development (Economics and region, 2018)
Introduction. The article analyzes the main indicators of social and economic development of regional clusters for the researching of their economic security level. The necessity and expediency of research of regional economic security are substantiated particularly on the basis of dynamics of social and economic indicators of regional development.Purpose of the study. To study social and economic indicators of the development of regions according to previously defined regional clusters of economic security.Methods: Methods of theoretical generalization were used to study and systematize the results of the study. Methods of analysis and synthesis in the study of the dynamics of indicators. The method of comparison allowed to determine the common and distinctive features of the research results of the basic social and economic indicators of regional clusters.Results The results of the analysis allowed to distinguish the differences between the regional clusters of economic security for each individual indicator of social and economic development. So, as a result of our research, we have determined that the best values of the indicators of social and economic development are the regional cluster with a level of economic security “good”, its indicator significance very differs from the value of indicators of other regional clusters. The cluster with a sufficient level of economic security has average values of indicators of social and economic development. The least of them is observed by a regional cluster with a satisfactory level of economic security.Conclusion The applied type of the presented research results is grounded in their practical application for the assessment of regional economic security. It is expedient to develop models for assessing regional economic security for the represented regional clusters in our further researches.
Keywords: region; regional cluster; social and economic indicators of the region; regional economic security